Bilingualism Gridlocked at the University of Kwazulu-Natal - Dianna Lynette Moodley (Nordic Journal of African Studies, 2009)
This paper situates itself in the context of proposed bi/multilingual Higher Education policy in post-apartheid South Africa. It provides a descriptive analysis of language-user attitudes toward a bilingual (English-isiZulu) medium of education at the University of KwaZulu-Natal (UKZN). The study postulates a dissonance between proposed bilingual policy and practice at UKZN due to resistance exhibited by the university community. Three objectives are pursued: (1) To report on the new bilingual policy currently implemented at the university, (2) To survey language attitudes prevalent among university affiliates, (3) To relate its conclusions to a re-evaluation of the implementation procedure of bilingual policy of UKZN, in line with the desirability of its constituents. A survey-questionnaire is administered to staff and students, probing the following salient factors: (a) language-use patterns (b) proficiency in isiZulu (c) language preferences (d) language attitudes and (e) awareness of language policy in Higher Education.